Environmental benefits of domestic solar energy systems - Kalogirou, Soteris A. (My University, 2004)
All nations of the world depend on fossil fuels for their energy needs. However the obligation to reduce CO2 and other gaseous emissions in order to be in conformity with the Kyoto agreement is the reason behind which countries turn to non-polluting renewable energy sources. In this paper the pollution caused by the burning of fossil fuels is initially presented followed by a study on the environmental protection offered by the two most widely used renewable energy systems, i.e. solar water heating and solar space heating. The results presented in this paper show that by using solar energy, considerable amounts of greenhouse polluting gasses are avoided. For the case of a domestic water heating system, the saving, compared to a conventional system, is about 80% with electricity or Diesel backup and is about 75% with both electricity and Diesel backup. In the case of space heating and hot water system the saving is about 40%. It should be noted, however, that in the latter, much greater quantities of pollutant gasses are avoided. Additionally, all systems investigated give positive and very promising financial characteristics. With respect to life cycle assessment of the systems, the energy spent for manufacture and installation of the solar systems is recouped in about 1.2 years, whereas the payback time with respect to emissions produced from the embodied energy required for the manufacture and installation of the systems varies from a few months to 9.5 years according to the fuel and the particular pollutant considered. Moreover, due to the higher solar contribution, solar water heating systems have much shorter payback times than solar space heating systems. It can, therefore, be concluded that solar energy systems offer significant protection to the environment and should be employed whenever possible in order to achieve a sustainable future.
Keywords: Solar water heating; Solar space heating; Environmental impact; Embodied energy